Fermentable Fiber Pectin Improves Intestinal Inflammation by Modulating Gut Microbial Metabolites and Inflammasome Activity. (29th May 2020) - Singh, Vishal; Yeoh, Beng San; Vijay-Kumar, Matam
Abstract: Objectives: Appreciation of the therapeutic benefits of fermentable dietary fibers (FDFs) in inflammatory bowel disease (IBD) is continuously growing. Herein, we examined the effect, and underlying mechanism(s), of FDF pectin on IBD development by using a preclinical model of intestinal inflammation. Methods: Chronic colitis was induced in dietary cellulose or pectin-fed WT mice by administering four weekly injections of interleukin (IL)-10 receptor neutralizing antibody. Mice were euthanized two weeks after the last injection, and colitis development was examined by gross colon appearance, serological, and histological markers. Results: The control group, which received insoluble fiber cellulose, developed extensive colonic inflammation as evident via colomegaly, splenomegaly, elevated pro-inflammatory cytokines including IL-1β, and distorted colonic crypts. Relative to cellulose, the level of inflammatory cytokines and histological scores were reduced in the pectin-fed mice. To understand the mechanism(s) by which dietary pectin alleviated intestinal inflammation, we analyzed the gut microbiota composition, its metabolic products, and inflammation regulators in our model. Compared to cellulose, pectin reduced the abundance of Verrucomicrobia and elevated acetate, an immune response modulator, in the cecal content. Inline, pectin-fed mice displayed reduced colonic IL-1β and heightened expression of inflammasome component NLRC4 in colonic epithelial crypts. Moreover, the colonic level of IL-1 receptor antagonist (IL-1Ra, a natural endogenous inhibitor of IL-1β), whose expression is partly regulated via NLRC4, was also elevated in mice fed pectin. The lack of pectin-mediated protective effects in NLRC4-deficient and IL-1Ra-deficient mice indicated that the NLRC4-IL-1Ra axis executes the beneficial effects of pectin during gut inflammation. Considering that IL-1Ra restrains the pro-inflammatory activity of IL-1β, this study suggests that pectin derived metabolites promote NLRC4 signaling, which augments IL-1Ra and thus limits IL-1β mediated colonic inflammation. Conclusions: Altogether, our study demonstrates that microbial metabolism, of FDFs, and NLRC4 inflammasome axis mediates the beneficial effects of pectin in the inflamed gut. Funding Sources: Career Development Award [ID# 597, 229] from Crohn's & Colitis Foundation (CCF).